2013
DOI: 10.1007/s11695-013-1137-2
|View full text |Cite
|
Sign up to set email alerts
|

The Duodenal–Jejunal Bypass Liner for the Treatment of Type 2 Diabetes Mellitus and/or Obesity: a Systematic Review

Abstract: This systematic literature review applies the GRADE approach to evaluate the efficacy and safety of the duodenal-jejunal bypass liner (DJBL) for the treatment of (a) patients with obesity ≥ grade II (with comorbidities) and (b) patients with type 2 diabetes mellitus + obesity ≥ grade I. We included ten studies with a total of 342 patients that primarily investigated a prototype of the DJBL. In high-grade obese patients, short-term excess weight loss was observed. For the remaining patient-relevant endpoints an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 14 publications
1
20
0
1
Order By: Relevance
“…One meta‐analysis and 1 review report that DJBL treatment is associated with significant weight reduction but no significant improvement in glycaemic control in obese patients with T2DM. We propose, however, that the lack of effect on glycaemic control in these analyses may be explained by the limited number of eligible studies.…”
Section: Discussionmentioning
confidence: 99%
“…One meta‐analysis and 1 review report that DJBL treatment is associated with significant weight reduction but no significant improvement in glycaemic control in obese patients with T2DM. We propose, however, that the lack of effect on glycaemic control in these analyses may be explained by the limited number of eligible studies.…”
Section: Discussionmentioning
confidence: 99%
“…HbA1c levels improved significantly to 7.0% in the Endobarrier group, and 85.3% of patients showed decreased postprandial glucose levels . However, in multiple meta‐analyses of other randomized control trials and observational studies, the pooled EWL compared to control or a sham procedure was shown to be closer to 9% to 12% after the procedure . One meta‐analysis failed to demonstrate a statistically significant difference in HbA1c between the procedure and control groups, whereas a review of only randomized control trials showed a significant decrease in HbA1c by 1.5% (95% confidence interval − 2.2, −0.78; P < 0.001) after 52 weeks compared with sham or control …”
Section: Small Bowel Therapiesmentioning
confidence: 97%
“…There is no reported mortality from the procedure. The early explantation rate of the EndoBarrier TM is 24% as demonstrated in a recent meta-analysis, 17 usually due to patient intolerance or device migration.…”
Section: Malabsorptive / Metabolic Devices and Proceduresmentioning
confidence: 97%